New Advances on Fermentation Processes 2020
DOI: 10.5772/intechopen.90029
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess Development for Human Mesenchymal Stem Cell Therapy Products

Abstract: Mesenchymal stem cells (MSCs) are advanced therapy medicinal products used in cell therapy applications. Several MSC products have already advanced to phase III clinical testing and market approval. The manufacturing of MSCs must comply with good manufacturing practice (GMP) from phase I in Europe and phase II in the US, but there are several unique challenges when cells are the therapeutic product. Any GMP-compliant process for the production of MSCs must include the expansion of cells in vitro to achieve a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 98 publications
0
11
0
2
Order By: Relevance
“…For example, CPPs for in vitro expansion of MPCs can be associated with cell density, age, medium, supplement, pH, temperature, and dissolved oxygen [ 19 ]; therefore, these parameters must be consistently monitored and controlled during the manufacturing of MPCs. Nonetheless, as mentioned above, tissue-derived MPCs still have the biological intricacy and heterogeneity from derived tissue sources or donors that can predispose each MPC to unique CQAs; hence, the equivalent CPPs must be distinguished case by case [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CPPs for in vitro expansion of MPCs can be associated with cell density, age, medium, supplement, pH, temperature, and dissolved oxygen [ 19 ]; therefore, these parameters must be consistently monitored and controlled during the manufacturing of MPCs. Nonetheless, as mentioned above, tissue-derived MPCs still have the biological intricacy and heterogeneity from derived tissue sources or donors that can predispose each MPC to unique CQAs; hence, the equivalent CPPs must be distinguished case by case [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This proliferative advantage may enable PSC-MPCs to be an alternative source for tissue-derived MPC products. MPCs for therapeutic applications require at least 1–2 × 10 6 cells per kilogram (kg), which means that at least 1 × 10 8 cells are needed for a single dose [ 20 ]. The number of isolated MPCs from tissue aspiration was dependent on their source, but the average number of cells was 0.4 × 10 6 MPCs per donation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the aging of MSC during expansion is a key limiting factor due older cells losing competence to behave as stem cells and having a tendency to enter senescence or even to undergo transformation. Aging MSC are more likely to activate a senescence-associated secretory phenotype and produce pro-inflammatory cytokines such as IL-1, IL-6, and IL-8, which inhibit the regenerative process [ 280 ]. It is also known that culture-expanded MSC, in general, lose their self-renewal capacity and multipotency progressively [ 281 , 282 ], which is a major limitation for research and potential treatments [ 1 , 283 ].…”
Section: Need Of New Strategies Of Msc Productionmentioning
confidence: 99%
“…For example, it was estimated that a production of 30 T-flasks each with a growth surface of 175 cm² would be required per patient, assuming each patient is dosed with 416 million cells and the harvesting efficiency is 8 × 10 4 cells/cm² [ 297 ]. However, for larger clinical trials with >100 patients, the resources required for cell culture would become insupportable (assuming the conditions stated above, a trial with 140 patients would require 4200 T-flasks filling 32 standard 160-L incubators and 9 full-time personnel to handle the cells) [ 280 ]. In addition, previous studies also reported that MSC proliferation and differentiation potential decreased when they reached a higher passage number [ 298 ].…”
Section: Need Of New Strategies Of Msc Productionmentioning
confidence: 99%
“…Despite the lack of legal regulations concerning the standardization of cell-based manufacturing processes, there are many recommendations and guidelines regarding quality assurance and the biological safety of such therapies, including the recommendations of ISCT for defining MSCs or the statement of the International Federation for Adipose Therapeutics and Science (IFATS) for the culture of AT-derived MSCs (AT-MSCs) [29]. Therefore, local regulatory authorities demand that the manufacturer determine the product's critical quality attributes (CQA), in particular its lot-to-lot consistency, identify potentially unsafe impurities by performing the quality control of raw materials, perform sterility and endotoxin tests [30], etc. Thus, the optimization of the protocols used for the processing and ex vivo expansion of AT-MSCs, the adjustment of the dose of cells necessary for the intended use of a medicinal product, and the preparation of the final product formulation so that it does not impact on the cells' biological activity and supports MSCs' capacity for interaction/regeneration with the target tissue represent real challenges and influence the efficiency of cell-based therapies.…”
Section: Introductionmentioning
confidence: 99%